2018
DOI: 10.1097/gox.0000000000001912
|View full text |Cite
|
Sign up to set email alerts
|

Liposuction Gives Complete Reduction of Arm Lymphedema following Breast Cancer Treatment—A 5-year Prospective Study in 105 Patients without Recurrence

Abstract: Background:Arm lymphedema is a well-recognized complication after breast cancer surgery that negatively impacts patients’ quality of life, both physiologically and psychologically. Lymph stasis and inflammation result in excess formation of adipose tissue, which makes removal of the deposited subcutaneous fat necessary to eliminate the excess volume. Liposuction, combined with postoperative controlled compression therapy (CCT), is the only treatment that gives complete reduction of the excess volume. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 46 publications
(46 reference statements)
0
61
0
1
Order By: Relevance
“…The indication for liposuction is fat hypertrophy in the affected extremities as shown on MRI. Proponents of liposuction demonstrate good volume reduction and no recurrence after 5 years (Hoffner et al, 2018a). The risks of liposuction include blood loss, hematoma, contour irregularity, and skin necrosis (Chen et al, 2019).…”
Section: Management Of Lymphedema By Multi-modalities Treatmentmentioning
confidence: 99%
“…The indication for liposuction is fat hypertrophy in the affected extremities as shown on MRI. Proponents of liposuction demonstrate good volume reduction and no recurrence after 5 years (Hoffner et al, 2018a). The risks of liposuction include blood loss, hematoma, contour irregularity, and skin necrosis (Chen et al, 2019).…”
Section: Management Of Lymphedema By Multi-modalities Treatmentmentioning
confidence: 99%
“…Volume reduction was greater in the combined group, but the difference was not statistically significant (P = 0.28). The outcome of maintaining reduced volume seven days after removing compression garments following the combination therapy is interesting because compression garments are needed to maintain the reduced volume achieved in patients treated only with lipoaspiration, and removing compression garments for one week one year post liposuction has led to an increase in volume up to 370 mL [14][15]. Some studies have suggested that lymph node transfer promotes regeneration of lymphatic tissue three months after surgery [16][17].…”
Section: Discussionmentioning
confidence: 99%
“…For best results, it is advised to wear the garment lifelong [57] . Hoffner et al [58] have shown a mean 5-year postoperative reduction of 117% ± 26% in the limb with lymphoedema compared with the healthy arm.…”
Section: Liposuctionmentioning
confidence: 97%